Tess of the d'Urbervilles [videorecording (DVD)] - Sharp, Ian, 1946-; Waddell, Justine; Flemyng, Jason; Milburn, Oliver; Hardy, Thomas, 1840-1928 (A & E Home Video : Distributed by New Video, 2003)
Tess Durbeyfield is a luminous beauty who is violated by one man and forsaken by another, but she refuses to remain a victim. Her struggle to endure despite the abandonment of her true love, and despite her desperate attempt to attain happiness, propels Tess toward a tragic end.